Development of Education of Backward Classes in Telangana 1947-97: The impact of welfare and educational programs on the educational development of backward classes in Telangana (1947-1997) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The Backward Classes/Communities seek after conventional exercises, for example, cows and sheep raising, hard stuff tapping, earthworks, angling, weaving, goldsmith, metal forger, metal smith, carpentry, stone cutting, clothing, ceramics, oil squeezing, basketry, hairdressing, fitting, coloring and so on. Government is actualizing different welfare, instructive and monetary improvement projects to inspire these groups; a portion of the conspicuous projects are BC welfare lodgings, private schools, post-metric expenses and educational cost charge repayment to the monetarily in reverse class understudies (EBC).